Grace and Scarcity: Gender Disparity in Today's Ballet Companies. Issue 4 (2nd October 2018) - Chow, Ivy
ABSTRACT: Examining issues of equity and access within today's ballet companies reveals three significant disparities. First, ballet is often regarded as a "feminine" art form made up of predominantly female dancers, but what is visible on stage masks a different reality off stage: Most leadership roles are occupied by men. Second, most of the choreographic structures and narratives of ballet present a man's point of view. Third, ballet studios are often dominated by female students and this exacerbates women's feelings of disposability and self-doubt when they join a company. They often feel they must acquiesce to a man's decisions or they could lose their jobs. Interviews were conducted with former or current principal dancers (the highest rank performer) to examine why this gender disparity exists. This article also offers pedagogical practices that can empower female students in studios and in higher education settings.